The Effects of Earthquakes on the Stock Market: The Case of Türkiye - Gedikli, Ayfer; Erdogan, Seyfettin; Ozdasli, Esma; Terzioglu, Hande Caliskan (International Journal of Economics and Financial Issues, 2025)
It is fact that the frequency of disasters—particularly earthquakes—have increased all over the world. These events have growing significant adverse effects on both national and global economies. The economic and financial costs caused by earthquakes are often substantial. Minimizing their devastating impact on financial markets, especially stock exchanges, has become a key priority for governments for the sake of financial system. The relationship between seismic events and economic indicators is therefore of considerable importance. The aim of this study is to comparatively analyze the effects of two major earthquakes experienced in Türkiye—the 1999 Marmara Earthquake and the 2023 Kahramanmaraş Earthquake—on the stock market. Utilizing the event study methodology, stock prices were compared across three timeframes: The days of the earthquakes, the days preceding the events, and the days following them. Later, volatility dynamics were examined using the GARCH (Generalized Autoregressive Conditional Heteroskedasticity) model. The empirical findings indicate that both earthquakes caused statistically significant short-term fluctuations in stock returns. The 1999 Marmara earthquake resulted in more distinct and sharp market fluctuations, whereas the 2023 Kahramanmaraş earthquake was followed by a comparatively milder recovery trend. The empirical results of the GARCH model highlighted that while there was volatility throughout the period, it showed a declining trend on the days the earthquakes occurred. This result can be explained by temporary market closures, investor reluctance to engage in trading, and a contraction in market liquidity.